1992
DOI: 10.1007/bf00296208
|View full text |Cite
|
Sign up to set email alerts
|

CT image analysis of the vertebral trabecular network in vivo

Abstract: A method of computed tomography (CT) image analysis of lumbar vertebrae has been developed, providing a visualization of the trabecular network as it is represented in a 1.5 mm-thick CT image. We measured the length of the network and the number of discontinuities found in the image. The ratio of these measurements was called the "trabecular fragmentation index" (TFI). CT images from 71 women between the ages of 50 and 59, and 94 women between the ages of 60 and 69 were divided into three groups according to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 13 publications
5
61
0
1
Order By: Relevance
“…There are a few cross-sectional studies using clinical CT scanners to assess vertebral trabecular structure in vivo (21)(22)(23) aiming at fracture discrimination or diagnosis of osteoporosis. In comparison with our work, all of these studies used larger voxel sizes, in the order of 400 m in plane, and a slice thickness of 1.0-1.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few cross-sectional studies using clinical CT scanners to assess vertebral trabecular structure in vivo (21)(22)(23) aiming at fracture discrimination or diagnosis of osteoporosis. In comparison with our work, all of these studies used larger voxel sizes, in the order of 400 m in plane, and a slice thickness of 1.0-1.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…no, (42) yes (43) Yes (125) Variable: yes, (84,166) no (22) BMD (g/cm 3 ; ±SD) Cancellous-vertebra 0.12-0.14 (82,167) 0.30-0.39 (58) 0.39-0.43 (171) 0.39-0.42 (107) 0.48-0.60 (58,82,168) Cancellous-distal femur 0.43-0.46 (168) 0.44 ± 0.16 (168) - (173) Similarity of bone attributes to humans ; ± SD (when vBMD data not available).…”
Section: Yesmentioning
confidence: 99%
“…Bone mineral density (BMD) has been shown to be one of the most important contributing factors to bone strength and a good predictor of fracture risks in osteoporosis [4,9,19,25,28]. However, many recent studies have shown that BMD alone may not be sufficient to determine the strength of cancellous bone and that the trabecular architecture may also be an important factor in determining bone strength and individual risk of fractures [3,5,11,33,34].…”
Section: Introductionmentioning
confidence: 99%